Medical Student POCUS Peer-to-Peer Teaching: Ready for Mainstream - Mazen El-Baba; Kathryn Corbett; Kate Dillon; Claire Heslop (University Library System, University of Pittsburgh, 2021)
Background: Point of care ultrasound (POCUS) is changing the face of clinical practice and medical education. Worldwide consensus based on expert opinion has advocated for POCUS teaching in undergraduate medical school curricula. Significant barriers, including lack of available instructors and limited resources, prevents medical learners from acquiring core competencies at most institutions. Here, we describe a peer-to-peer learning POCUS workshop and advocate for the use of this type of training to meet the demands of POCUS learning. Methods: A two-day POCUS workshop was held in Toronto, Ontario with twenty-six medical student participants. The workshop was structured according to a graduated model of POCUS skill development, beginning with didactic teaching, then progressing to hands-on peer-to-peer teaching, and finishing with competency evaluation by POCUS experts. Participants completed pre-and post-workshop surveys regarding prior POCUS teaching and exposure, self-reported skill development, and feedback on the workshop itself. Results: Of the 20 respondents to the questionnaire, 70% had prior POCUS exposure, with 85% of these individuals having less than 5 hours of prior POCUS education. Eighty-five percent of students reported that the organization of the course allowed them to participate fully, and 95% of participants indicated that peer-to-peer learning was effective. Conclusion: These findings suggest that peer-to-peer POCUS teaching is an effective learning method to acquire and consolidate well-established POCUS competencies. This initiative is scalable and could be applied to all learners in various disciplines. As such, we recommend medical schools consider integration of peer-to-peer POCUS teaching into longitudinal clerkship training programs, and transition-to-residency courses.